Suing Alma Mater - Olivas, Michael A. (Johns Hopkins University Press, 2022)
This careful reading of six legal cases in American higher education is an essential primer for understanding contemporary litigation.Winner of the Steven S. Goldberg Award for Distinguished Scholarship in Education Law of the Education Law AssociationAlthough much has been written about U.S. Supreme Court decisions involving higher education, little has been said about the foundational case law and litigation patterns emerging from the lower courts. As universities become increasingly legislated, regulated, and litigious, campuses have become testing grounds for a host of constitutional challenges. From faculty and student free speech to race- or religion-based admissions policies, Suing Alma Mater describes the key issues at play in higher education law.Eminent legal scholar Michael A. Olivas considers higher education litigation in the latter half of the twentieth century and the rise of "purposive organizations,” like the American Civil Liberties Union and the Alliance Defense Fund (now known as the Alliance Defending Freedom), that exist to advance litigation. He reviews more than 120 college cases brought before the Supreme Court in the past fifty years and then discusses six key cases in depth. Suing Alma Mater provides a clear-eyed perspective on the legal issues facing higher education today.